Synthesis and structure-activity relationships for some novel diflapolin derivatives with benzimidazole subunit - Lisa Vieider; Eva Zoeller; Erik Romp; Martin Schoenthaler; Victor Hernández-Olmos; Veronika Temml; Thomas Hasenoehrl; Daniela Schuster; Oliver Werz; Ulrike Garscha; Barbara Matuszczak (Taylor & Francis Group, 2022)
A series of derivatives of the potent dual soluble epoxide hydrolase (sEH)/5-lipoxygenase-activating protein (FLAP) inhibitor diflapolin was designed, synthesised, and characterised. These novel compounds, which contain a benzimidazole subunit were evaluated for their inhibitory activity against sEH and FLAP. Molecular modelling tools were applied to analyse structure-activity relationships (SAR) on both targets and to predict solubility and gastrointestinal (GI) absorption. The most promising dual inhibitors of these series are 5a, 6b, and 6c.